A new species of planthopper in the genus Haplaxius (Hemiptera: Fulgoroidea: Cixiidae) from disturbed submontane rainforest in Jamaica - Bahder, Brian W.; Myrie, Wayne; Helmick, Ericka E.; Bartlett, Charles R. (Zootaxa, 2023)
Haplaxius is a large genus of cixiid planthopper found in the New World. The genus is of particular interest due to the ability of H. crudus to transmit the phytoplasmas for lethal decline in various palm species, primarily in the Caribbean and Florida, U.S.A. During recent vector survey work in Jamaica, a specimen was collected at Castleton Botanic Garden and determined to be a new species of Haplaxius. The novel taxon is herein described, Haplaxius fornicus sp. n., and corresponding DNA sequence data is provided for the barcoding region of the cytochrome c oxidase subunit I (COI) gene, 18S rRNA gene, and histone 3 (H3) gene. An updated phylogeny of the genus is provided with currently available taxa demonstrating additional support for the placement of H. fornicus sp. n. in Haplaxius.